MSU Work Related Learning web-based trip scheduling system - Dube, Fungai (Midlands State University, 2020)
Technology is changing rapidly and there is need to adjust so as to improve the economy and how businesses operate in Zimbabwe. This research gives a detailed overview of Work related learning with the main thrust of solving current problems in their way of operation, at the same time with the main of implementing new technologies in Zimbabwe that will help improve our economy through the improvement of business operations. The system will enable the Work related learning department to work with a computerized system that is more efficient and reliable at any time. The system is web-based thus users can access it at any location at any time. Major reason for carrying out the research is to curb the problems of the current system at the same time increasing organizational competence.